Matrix correction with Compton to Rayleigh ratio in a plant–soil–rock interface analysis using a laboratory micro‐XRF. (11th July 2019) - Shen, Yating; Luo, Liqiang; Song, Yufang; Liu, Jian; Lao, Changling; Sun, Menghe; Yang, Wenlei
Abstract : Biogeochemistry interface process in a plant–soil (rock) system normally takes a key role in environmental processes. It involves complex mediums relating with complex crucial physical, chemical, and biological interactions. Accurate description of element distribution characteristics in interfaces and combination media is the prerequisite for revealing elements transfer and transformation processes. In situ micro‐X‐ray fluorescence is used here to describe the localizations of elements in a bryophyte–soil–rock interface involving biological (plant) and geological (soil and rock) matrixes. It is shown that matrix effects get great influence on the localization characteristics in this interface. Spectra without matrix corrections shows that Zn, Cu, Fe, Ca, and K reach maximum concentrations in different interface layers. Compton to Rayleigh ratio (Com/Ray), relating with mean atomic number (mean Z) and mass attenuation coefficients, has been applied in matrix correction, whereas other correction methods like multiplied or divided by Com or Ray were compared here too. The results show that the correction method with Ray*Ray/Com is more suitable for describing reasonable Ca, Mn, Fe, Zn, Cu, and Pb localization characteristics in this interface, whereas correction with Ray/Com is better for K. The localization characters after ideal corrections show that K, Ca, Pb, Zn, and Cu reach their maximum peaks at the soil layer in the interface, which are much more reasonable than the results without corrections.